2017
DOI: 10.1249/mss.0000000000001170
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Maximal Oxygen Uptake in Obese and Nonobese Children

Abstract: Purpose The purpose of this study was to examine whether a supramaximal constant load verification test at 105% of the highest work rate would yield a higher V̇O2max when compared with an incremental test in 10 – 12 year old nonobese and obese children. Methods Nine non-obese (BMI percentile: 57.5 ± 23.2) and nine obese (BMI percentile: 97.9 ± 1.4) children completed a two-test protocol that included an incremental test followed 15 minutes later by a supramaximal constant-load verification test. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 38 publications
3
52
3
Order By: Relevance
“…Bland‐Altman analysis showed error bias of 63 mLO 2 ·min −1 which suggest that GXT routinely underestimate normalV˙O2max by that magnitude. This bias is lower than the one reported by Bhammar et al, (ie, 118 mLO 2 ·min −1 ) but higher than Sawyer et al, (ie, 40 mLO 2 ·min −1 ). Astorino and DeRevere in active young adults reported negative bias (−54 and −41 mL·min −1 ), indicating that VerT could underestimate GXT normalV˙O2max .…”
Section: Perspectivecontrasting
confidence: 64%
See 3 more Smart Citations
“…Bland‐Altman analysis showed error bias of 63 mLO 2 ·min −1 which suggest that GXT routinely underestimate normalV˙O2max by that magnitude. This bias is lower than the one reported by Bhammar et al, (ie, 118 mLO 2 ·min −1 ) but higher than Sawyer et al, (ie, 40 mLO 2 ·min −1 ). Astorino and DeRevere in active young adults reported negative bias (−54 and −41 mL·min −1 ), indicating that VerT could underestimate GXT normalV˙O2max .…”
Section: Perspectivecontrasting
confidence: 64%
“…Using these parameters, we found high test‐retest reproducibility in VerT in a subset of eight of our untrained MetS individuals with obesity. VerT time to exhaustion (2.1 ± 0.4 minutes; Table ) was similar to previous studies . Thus, a VerT procedure as the present (110% work rate after 15 minutes of recovery and a 2 minutes or warm‐up) seems to be reproducible and valid in unfit MetS individuals with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() demonstrated that overweight and obese adults show ‘true’ VO 2 max in response to VER, which suggests that obesity does not affect achievement of VO 2 max. However, recent findings in normal weight and obese children show that VER elicited higher VO 2 max than INC (Bhammar et al ., ). Our data show that compared to more fit individuals, persons classified as low fitness are more likely to reveal lower VO 2 max in response to INC versus VER, as no subject with VO 2 max≥50 ml kg −1 min −1 showed higher VO 2 max in response to VER.…”
Section: Discussionmentioning
confidence: 97%